ANALISIS HUKUM PIDANA ADAT NIAS DALAM MENYELESAIKAN KASUS PENCURIAN - Hepy Krisman Laia; Muhammad Yasid (JURNAL RETENTUM, 2020)
The formation of customary law and customary sanctions is inseparable from the result of a violation or crime which according to customary law is seen as a crime that can damage the sense of comfort and sense of peace in social life, so that the perpetrators and offenders are subject to customary sanctions which are a retribution or lesson for the perpetrator of crime so as not to repeat it again. Customary law was applied by the Dutch to the Bumi Putera Group with the assumption that customary law was in accordance with the mystical atmosphere of the Indonesian people at that time, one part of customary law is customary criminal law. Customary criminal law today is still alive in the community, even though the Criminal Code is valid as a positive law.